Village-life.com - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Village-life.com, New Scientist, vol. 174 issue 2341, 4 May 2002, page 44 Unlike the thousands of other Indian fishermen who venture into the Bay of Bengal, Raja knows the latest weather forecasts and wave-height predictions, downloaded fro